Plastic gear loss estimates from a major Australian pot fishery. (31st December 2022) - Bornt, Katrina; How, Jason; de Lestang, Simon; Linge, Kathryn; Hovey, Renae; Langlois, Tim
Abstract: The quantity of plastic fishing gear lost to the ocean remains largely undocumented despite its importance for understanding the magnitude of fishery contributions to plastic marine debris and mitigating contamination at the source. This study estimated plastic gear loss from a major Australian pot fishery by interviewing 50 commercial fishers from the West Coast Rock Lobster Managed Fishery in 2021 to document the plastic gear components used, the number of pots lost, and the causes for gear loss. The estimated annual percentage of gear lost (10.8%) and rate of "active" gear loss by fishing effort (0.2%) were lower than global estimates for other pot fisheries indicating that plastic gear loss from this commercial fishery is relatively low. Plastic gear loss was attributed to rope (47.0%), pot components (30.7%), and floats (22.3%), of which 78.0% were polypropylene and polyethylene. The composition of pots, measures used to prevent gear loss, and changes to management could influence plastic gear loss from this fishery. This is the first study to examine plastic gear loss from an Australian pot fishery with a dynamic approach that provides robust estimates for better understanding plastic gear loss from fisheries and informing plastic mitigation efforts.